An unpublished version of Leonardo Bruni’s Vita di Dante transcribed and glossed by Ser Piero Bonaccorsi. - Seriacopi, Massimo (Cuadernos de Filología Italiana, 2003)
The author proposes a critical edition of an unpublished editing of Dante’s Life by the chancellor Leonardo Bruni, extant in a codex inside the Biblioteca Mediceo Laurenziana of Florence, and copied by Ser Piero Bonaccorsi in 1440, and by the same embellished with interesting remarks and bordering glosses, sometimes showing a specific cultural ground, besides bringing some critical and historical news that can assume a special importance, in a linguistic level, for instance.